CONFIGURING SAFE INDUSTRIAL ROBOT WORK CELL IN MANUFACTURING INDUSTRY - A Rahman, Muhamad Arfauz; Osman, Nor Suriyanti; Heng Boon, Chew; Poh, Gordon Ling Teck; Abdul Rahman, Azrul Azwan; Bali Mohamad, Bashir Mohamad; Kamsani, Silah Hayati; Mohamad, Effendi; Zaini, Zainul Azereen; Ab Rahman, Mohd Fairuz (Journal of Advanced Manufacturing Technology (JAMT), 2016)
This paper presents a proposed framework for determining workspace and safe working area of industrial robot. The focus of this work is on providing a fast and easy configuration approach for safe robot working area. In order to design and develop the proposed Framework for the Robotic Work Cell Configuration (FraRWCC), a research and case study on industrial robot and its specification were carried out and described briefly in this paper. A study on a computer program and CAD software has been conducted to enhance a knowledge and information used in this project. Solid Work software is used to create 3D robot workspace while Microsoft Visual Basic. Net is chosen to program a set of object-oriented programming for creating a completed user interface. User may interact with the developed user interface to determine robot workspace and safe working area. By using this computer program, it may reduce the time for installing the industrial robot and potentially avoids any accident during the robot operation.